MENGEMBANGKAN ASPEK KOGNITIF MENGENAL BENTUK GEOMETRI MENGGUNAKAN MODEL PBL, EXAMPLE NON EXAMPLE DAN MEDIA PAPINBAR - Novianti, Novianti; Novitawati, Novitawati (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research is motivated by the low cognitive ability in recognizing geometric shapes in group B children of Kenanga Kindergarten, Banjarmasin. To overcome this problem, a problem-based learning model, example non-example, and papinbar media can be used. The purpose of this study is to describe teacher activities, children's activities, and analyze the results of children's cognitive development achievements, especially in recognizing geometric shapes. This study uses a qualitative approach and Classroom Action Research (CAR) with 4 meetings. The results of the study show that teacher activities have implemented the steps of the learning model with a score of 31 with a percentage of 97% in the